2009
DOI: 10.1111/j.1365-2265.2008.03393.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐gravid physical activity and reduced risk of glucose intolerance in pregnancy: the role of insulin sensitivity

Abstract: Objective-Pre-gravid physical activity has been associated with a reduced risk of gestational diabetes mellitus (GDM), although neither the types of exercise nor the physiologic mechanisms underlying this protective effect have been well studied. Thus, we sought to study the relationships between types of pre-gravid physical activity and metabolic parameters in pregnancy, including glucose tolerance, insulin sensitivity and beta-cell function.Design/Patients/Measurements-851 women underwent a glucose challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 42 publications
2
34
1
2
Order By: Relevance
“…Pregravid physical activity in the year before pregnancy was assessed using the Baecke questionnaire, an established instrument that has been extensively validated in several populations, including women of childbearing age (12,13). This questionnaire was completed during the OGTT (i.e., prior to knowing their gestational glucose tolerance status) (14,15). The Baecke questionnaire measures total physical activity and its three component domains: occupation-associated activity (work index), sport-related physical activity (sport index), and nonsport leisure-time activity (leisure-time index).…”
Section: Methodsmentioning
confidence: 99%
“…Pregravid physical activity in the year before pregnancy was assessed using the Baecke questionnaire, an established instrument that has been extensively validated in several populations, including women of childbearing age (12,13). This questionnaire was completed during the OGTT (i.e., prior to knowing their gestational glucose tolerance status) (14,15). The Baecke questionnaire measures total physical activity and its three component domains: occupation-associated activity (work index), sport-related physical activity (sport index), and nonsport leisure-time activity (leisure-time index).…”
Section: Methodsmentioning
confidence: 99%
“…Dempsey et al reported that women who participated in any physical activity during the year before getting pregnant experienced a 56% risk reduction in GDM compared with inactive women, but those who engaged in physical activity during both time periods experienced a 69% reduced risk (Dempsey et al, 2004b). It has also been shown that pre-gravid physical activity (vigorous activity) was associated with a reduced risk of IGT in pregnancy, an effect likely mediated by enhanced insulin sensitivity (Retnakaran et al, 2009). Similar results were found when investigating the effect of physical activity during pregnancy.…”
Section: Maternal Physical Activity Is Associated With Reduced Risk Omentioning
confidence: 98%
“…Az inzulinszenzitivitás fokozá-sával és a glükóztolerancia javításával, számos mechanizmuson keresztül, a fizikai aktivitásnak jótékony hatása van az inzulinrezisztencia több aspektusára [35]. Két vizsgálat a terhesség előtti és alatti fizikai aktivitás és GDM kockázatcsökkenése között pozitív összefüggést igazolt [36,37]. Ez a hatás fokozódik a fizikai aktivitás intenzitásának és idejének növelésével.…”
Section: Fizikai Aktivitásunclassified